2020
DOI: 10.1038/s41379-019-0442-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of IDH2 R172 hotspot mutations in breast papillary neoplasms: applications in the diagnosis of tall cell carcinoma with reverse polarity

Abstract: Tall cell carcinoma with reverse polarity is a rare subtype of breast carcinoma with solid and papillary growth and nuclear features reminiscent of those of the tall cell variant of papillary thyroid carcinoma. These tumors harbor recurrent IDH2 R172 hotspot mutations or TET2 mutations, co-occurring with mutations in PI3K pathway genes. Diagnosis of tall cell carcinomas with reverse polarity is challenging in view of its rarity and the range of differential diagnosis. We sought to determine the sensitivity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 30 publications
1
38
0
1
Order By: Relevance
“…Lozada et al reported that high frequencies of IDH2 R172 and PIK3CA hotspot mutations were present in their patient cohort (12). Pareja et al further demonstrated that the immunohistochemical analysis of IDH2 R172 was highly sensitive and specific for the detection of IDH2 R172 hotspot mutations, and was likely suitable as a diagnostic tool for evaluating the excisions and core needle biopsy A B materials of TCCRP (14). Notably, IDH2 R120, rather than the IDH2 R172 mutation, was detected in our case, a finding that has not been reported in previous studies.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Lozada et al reported that high frequencies of IDH2 R172 and PIK3CA hotspot mutations were present in their patient cohort (12). Pareja et al further demonstrated that the immunohistochemical analysis of IDH2 R172 was highly sensitive and specific for the detection of IDH2 R172 hotspot mutations, and was likely suitable as a diagnostic tool for evaluating the excisions and core needle biopsy A B materials of TCCRP (14). Notably, IDH2 R120, rather than the IDH2 R172 mutation, was detected in our case, a finding that has not been reported in previous studies.…”
Section: Discussionmentioning
confidence: 96%
“…As the incidence of TCCRP is low, it is difficult to conduct a valuable retrospective analysis of the disease from independent case reports or small-scale cohort studies. However, we comprehensively reviewed relevant articles (15 in total) published from 2003 to date, and extracted key information including demographic, clinicopathologic, and immunohistochemical data, along with hotspot gene sequencing results (Tables S1,S2), to detect meaningful patterns by expanding the sample size (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). After eliminating the repeated cases from among the abovementioned studies, a total of 74 cases (including this present case) remained.…”
Section: Discussionmentioning
confidence: 99%
“…In the blood of pancreatic cancer patients, the concentrations of CA19.9, Lea, and Leb antigens appear to depend on the following two main factors: (1) the reabsorption of the antigens by the circulating blood, which, in turn, is probably a side effect of the duct obstruction and/or loss of polarity; and (2) the production of each antigen by normal pancreatic ducts. Consequently, the following two crucial aspects need to be investigated in more detail: the obstruction and loss of polarity, which has been poorly investigated so far in gastrointestinal tumors [71] but has already been studied in other organs [72][73][74], and the individual expression pattern of antigens, which is the result of the expression of genetically and epigenetically regulated glycosyltransferases, namely FUT1-3 and B3GALT5.…”
Section: A Proposed Model Of Circulating Ca199 and Type 1 Chain Lewimentioning
confidence: 99%
“…Although IDH2 mutations are commonly identified in many tumors such as secondary gliomas, myeloid malignancy, cholangiocarcinoma, microsatellite stable colorectal cancer, chondrosarcoma etc., they are infrequent among breast tumors but are typically seen in TCCRP (7,(13)(14)(15)(16)(17). Pareja et al demonstrated that immunohistochemistry using a monoclonal antibody against IDH2 R172S (Clone -11C8B1) is sensitive and specific for TCCRP harboring the IDH2 R172 hotspot mutation (18). Genetic alterations prevalent in papillary thyroid carcinoma like RET/PTC rearrangements and BRAF mutations (18,19) are almost always absent in TCCRP.…”
Section: Discussionmentioning
confidence: 99%